Citation for Professor Andrzej Rakowski - MIŚKIEWICZ, Andrzej; Fidecki, Tadeusz; Łętowski, Tomasz; Smurzyński, Jacek; Szlifirski, Krzysztof; Żera, Jan (Archives of Acoustics, 2007)
Anybody who has even a passing interest in auditory perception is familiar with the work and publications of Professor Andrzej Rakowski who is an internationally acclaimed authority on musical acoustics and psychoacoustics. This citation serves a symbolic tribute to Professor Rakowski on the 50th anniversary of his scientific career.Andrzej Rakowski was born in Warsaw, Poland, on 16 June 1931. In 1957, he received a Master of Science degree in electronic communication from the Warsaw University of Technology and a Master of Arts degree in music theory from then the State School of Music in Warsaw, now called The Fryderyk Chopin Academy of Music, in 1958. His contributions to acoustic research began during his postgraduate fellowship at Durham University, King's College, Newcastle upon Thyne, in England (1958/59), where he studied acoustics of musical instruments with E. G. Richardson. He received a doctoral degree in electronic communication from the Warsaw University of Technology in 1963, a second doctoral degree (habilitation) in art sciences (musicology) from the University of Warsaw in 1977, and became a full-professor in 1982, as conferred by the President of the Republic of Poland.